A doublestep extragradient method for solving a resource management problem - A. V. Zykina; N. V. Melenchuk (Моделирование и анализ информационных систем)
In the article is proposed a doublestep extragradient method for solving nonintrinsic problems of linear programming, variational inequalities and some related problems. The convergence of this method in general case is proved. The convergence of the method at the rate of geometric progression is proved for the problems of linear programming.